2018
DOI: 10.1007/s40520-018-0930-0
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity among hospitalised older people: insights from upper and lower limb accelerometry

Abstract: BackgroundFew studies have explored the activity levels of hospitalised older people and the intra-daily activity patterns in this group have not been described.AimsTo describe the quantity and daily pattern of physical activity among hospitalised older people using two accelerometers: the ankle-worn StepWatch Activity Monitor (SAM), and the wrist-worn GENEActiv.MethodsThis cross-sectional observational study was conducted on the acute medical wards for older people in one UK hospital. Inclusion criteria: part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 27 publications
(32 reference statements)
8
56
0
1
Order By: Relevance
“…Patients spent a median of approximately 1 hour/day on PA, a value lower than the 4.2 hours/day reported by Lim et al's study (12), who analyzed locomotion in 38 acutely hospitalized older patients (median age of 87.8 years). Conversely, another study reported only 43 min per day spent standing or walking (32) in a sample of 45 hospitalized older patients (median age 74.2 years) capable of walking independently pre-admission.…”
Section: Physical Activity Levels and Distribution Throughout The Daymentioning
confidence: 61%
See 2 more Smart Citations
“…Patients spent a median of approximately 1 hour/day on PA, a value lower than the 4.2 hours/day reported by Lim et al's study (12), who analyzed locomotion in 38 acutely hospitalized older patients (median age of 87.8 years). Conversely, another study reported only 43 min per day spent standing or walking (32) in a sample of 45 hospitalized older patients (median age 74.2 years) capable of walking independently pre-admission.…”
Section: Physical Activity Levels and Distribution Throughout The Daymentioning
confidence: 61%
“…The strengths of this study are its large sample size, its broad inclusion criteria, the use of accelerometers to assess PA and the large number of PA hours recorded. Regarding sample size, this study is the largest when compared to other studies in Europe (12,13,(16)(17)(18)41), the USA (20,21,32) and Australia (14,19).…”
Section: Strengths and Limitationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Bedfast (con ned to bed) 2. Chairfast (ability to walk severely limited or non-existent) 3. Walks occasionally (walks occasionally during day, but for very short distances, and spends majority of each shift in bed or chair) 4.…”
Section: Methodsmentioning
confidence: 99%
“…Inpatients have been found to have very low physical activity with a median of 478-1,158 daily steps, compared to a normal of 5,000-6,000 steps for most individuals over 65. [3][4][5][6][7] Affordable consumer wearable devices that continuously measure activity, sleep and vital signs may provide valuable information that could improve the care of inpatients. These devices could provide more frequent monitoring to detect deterioration earlier and avoid failures to rescue.…”
Section: Introductionmentioning
confidence: 99%